Economic Implications of Deeper Asian Integration - Joseph Francis Francois; Ganeshan Wignaraja (Johannes Kepler University of Linz, Department of Economics, 2008)
The Asian countries are once again focused on options for large, comprehensive regional integration schemes. In this paper we explore the implications of such broad-based regional trade initiatives in Asia, highlighting the bridging of the East and South Asian economies. We place emphasis on the alternative prospects for insider and outsider countries. We work with a global general equilibrium model of the world economy, benchmarked to a projected 2017 sets of trade and production patterns. We also work with gravity-model based estimates of trade costs linked to infrastructure, and of barriers to trade in services. Taking these estimates, along with tariffs, into our CGE model, we examine regionally narrow and broad agreements, all centered on extending the reach of ASEAN to include free trade agreements with combinations of the northeast Asian economies (PRC, Japan, Korea) and also the South Asian economies. We focus on a stylized FTA that includes goods, services, and some aspects of trade cost reduction through trade facilitation and related infrastructure improvements. What matters most for East Asia is that China, Japan, and Korea be brought into any scheme for deeper regional integration. This matter alone drives most of the income and trade effects in the East Asia region across all of our scenarios. The inclusion of the South Asian economies in a broader regional agreement sees gains for the East Asian and South Asian economies. Most of the East Asian gains follow directly from Indian participation. The other South Asian players thus stand to benefit if India looks East and they are a part of the program, and to lose if they are not. Interestingly, we find that with the widest of agreements, the insiders benefit substantively in terms of trade and income while the aggregate impact on outside countries is negligible. Broadly speaking, a pan-Asian regional agreement would appear to cover enough countries, with a great enough diversity in production and incomes, to actually allow for regional gains without substantive third-country losses. However, realizing such potential requires overcoming a proven regional tendency to circumscribe trade concessions with rules of origin, NTBs, and exclusion lists. The more likely outcome, a spider web of bilateral agreements, carries with it the prospect of significant outsider costs (i.e. losses) both within and outside the region.
Keywords: F13; F17; 330; regionalism; Asia FTAs; ASEAN; preferential trade; gravity model of services trade; trade costs and infrastructure; Wirtschaftsintegration; Regionalismus; Freihandelszone; Außenhandelsliberalisierung; Außenhandelspräferenz; Asien